Forecasting The Supply And Price Of Red Cayenne Pepper In Kramat Jati Main Market - Elvira Suci Latifa; Slamet Abadi; I Putu Eka Wijaya (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: The objective of this study is to determine the best forecast for supply and price, make a forecast for supply and price for the next 6 months, and analyze the effect of supply on the price of red cayenne pepper at PIKJ. Methodology: A qualitative and quantitative descriptive approach was used. Data collection techniques involved interviewing red chili pepper traders at the Kramat Jati Central Market (PIKJ), which supported the results of the quantitative data processing. Forecasting the growth of supply and average prices of red cayenne pepper from January 2020 to May 2023 was conducted using data obtained from PIKJ. Simple regression analysis was also conducted to test the effect of supply on the price of red cayenne peppers. Results: The forecast of supply and prices for the next 6 months shows that the price of cayenne pepper at PIKJ from June 2023 to November 2023 will experience an upward trend, which is influenced by fluctuating supply. Findings: The analysis of the effect of supply on the price of red cayenne pepper at PIKJ shows a significant result. Conclusion: Supply has a significant effect on prices circulating in the community. The availability of floor and ceiling price policies could be one solution to the fluctuation of red chili pepper prices. Addition of variables besides supply to examine other factors affecting the price of red chili peppers. Type of paper: Research Article.